Microstructural and mineralogical characterization of biomass ash from burning in jeans laundry boilers (Research, Society and Development, 2022)
The state of Pernambuco stands out on the national scene as an important pole of the clothing sector, due to the industrial activities carried out in the Agreste Local Productive Arrangement of the state. Within this context are the jeans laundries, responsible for the processing of the pieces and which depend on a large generation of steam for their processes. Laundries consume significant amounts of firewood per month for combustion in boilers, generating biomass ash as secondary waste, which has been shown to be a problem in terms of its destination, due to irregular disposal in the region. This work aims to study the microscopy of concrete with incorporation of biomass ash, from the boiler of a laundry in the Agreste region of Pernambuco. To carry out the work, the ash was collected in a laundry located in Caruaru-PE, whose main energy source is mesquite firewood, and chemical characterizations of the concrete components were carried out, techniques such as X-ray diffraction were used. (XRD), for mineralogical determination, and scanning electron microscopy (SEM), for microstructural characterization. It was verified that the increase in the occurrence of late ettringite in the face of the addition of ash in the material, in addition to the possible influence of the type of cement.